The Key Success Factors of Collaborative Network for Enhancing Green Tourism in Khao Kho District, Phetchaboon Province - Nonsiri, Petchsri; Narongrit, Chada (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
Khao Kho is renowned nationally as a relaxing tourist destination in Thailand. Since a decade, this place has been intensively driven by conventional tourism. The rapid growth of tourists in the last five years causes a negative impact to natural environment; especially Khao Kho is a fragile area of limitation in land utilizations. This research aimed to build the Green Tourism Destination through the collaborative network of tourism actors. The paper, therefore examined (1) the Green Tourism Development Process and (2) the key success factors of the collaborative network using the qualitative method: observation, focus group and in-depth interview with 135 stakeholders and members of the collaborative network. The lessons learnt from the project were 1) A cause of the unique characteristic of Khao Kho, spatial research and destination design phases had been done carefully; Double Diamond Model was employed into this process. It is evident that the key success factors of the collaborative network relied on the collaboration between all stakeholders in the area, especially the public sector who has a role of importance and power. 2) To sustain member’s relationship, one of critical success factor is the green tourism activities should operate regularly and continuously. The main contribution of this research is the enhancement of the collaboration among tourism actors in Khao Kho through the learning processes in Green Tourism activities.